Aqueous Medium Synthesis Route for Randomly Stacked Molybdenum Disulfide. (18th April 2013) - Panigrahi, Pravas Kumar; Pathak, Amita
Abstract : Synthesis of poorly crystalline, randomly oriented rag-like structures of molybdenum disulfide has been reported starting from aqueous solutions of ammonium molybdate, and thioacetamide in presence of sodium dodecyl sulfate via calcination of the amorphous precipitates, obtained through acidification of the in situ generated intermediate of ammonium tetrathiomolybdate. X-ray photoelectron spectroscopy, UV-visible spectroscopy, and X-ray diffraction of the calcined samples reveal the formation of single-phase MoS2, while the amorphous precipitates have been found to be a mixture of Mo2 S5, MoS3, and a trace amount of H2 MoS4 . Highly folded and disordered layers of rag-like MoS2 have been confirmed through high-resolution transmission electron microscopy. The electrical conductivity for the cold pressed pellet of the MoS2 sample is found to be significantly higher than that of 2H-MoS2 and increases further on annealing.